Media addiction in children and adolescents—a study protocol for development, piloting and evaluation of a sustainable, integrative rehabilitation program (MeKi) - Fahrenkrog, S.; Rittmann, L. M.; Klüpfel, L.; Delfs, S.; Stumm, J. (Frontiers in Adolescent Medicine, 2025)
IntroductionThe proportion of children and young people in Germany who have problematic media use has increased, particularly as a result of the coronavirus pandemic. The presence of comorbidities such as anxiety disorders, depression, sleep disorders, impulsivity and lack of social skills are interdependent with media addiction. Medical rehabilitation is suitable for the long-term care of children and adolescents with media addiction. As part of the MeKi study, a rehabilitation program for children and adolescents with media addiction is being developed and piloted in a cooperating rehabilitation clinic. The trial is registered under DRKS-ID: DRKS00034461, Medienabhängigkeit bei Kindern und Jugendlichen—Entwicklung, Pilotierung und Evaluation eines nachhaltigen, integrativen Rehabilitationskonzepts.Methodes and analysisAs part of a mixed methods design a multimodal rehabilitation concept for children and adolescents with media addiction will be developed in a preparation phase based on the results of a scoping review as well as interviews and focus groups with affected children and adolescents, their parents and experts. In a trial phase the concept will be implemented with a planned sample of 80 Children and adolescents over a period of 1.5 years and evaluated by means of a results evaluation using a questionnaire survey and a process evaluation using interviews and focus groups.DiscussionThe lack of a standardized definition for problematic media use in children and adolescents complicates both the scientific discourse and the practical care of those affected. Furthermore, there are currently only a few therapeutic offers and these are only available in the acute sector. The development and piloting of a rehabilitation program for children and adolescents with media addiction is intended to provide sustainable rehabilitative care, which is to be transferred to other clinics after the end of the project.Trial registrationThe trial is registered under DRKS-ID: DRKS00034461, Medienabhängigkeit bei Kindern und Jugendlichen—Entwicklung, Pilotierung und Evaluation eines nachhaltigen, integrativen Rehabilitationskonzepts.